PENGARUH FOOTBATH TREATMENT TERHADAP NYERI POST SECTIO CAESAREA DI RUANG MELATI RSUD DR SOEKARDJO TASIKMALAYA TAHUN 2019 - Detty Chotimah; Yulia Herliani; Endang Astiriyani (JURNAL KEBIDANAN KESTRA (JKK), 2020)
Sectio caesarea is a surgical procedure in giving birth with an abdominal incision and uterus that have higher morbidity than normal childbirth. Foot bath treatment is one part of post natal spa can release endorphins in the brain which is a natural pain reliever. The purpose of this research is to determine the effect of foot bath treatment on post SC pain in Melati room RSUD dr Soekardjo Tasikmalaya. This research was used pre eksperimental with pretest posttest design. The research instrument used Numerical Rating Scale (NRS). Sampling technique was used purposive sampling with 30 respondents. Foot bath treatment is done for 15 minutes. The analyzed was by Wilcoxon Signed Rank Test. The result of this research showed that the scale of pain before getting foot bath treatment is mostly moderate pain as many as 26 peoples (87,7%). The scale of pain after getting foot bath treatment is mostly mild pain as many as 25 peoples (83,3%). The result of the statistical test showed p value 0,000 <0,05 it means there is an effect of foot bath treatment to post SC pain.